Brasil: Acima de Tudo!! The Brazilian Armed Forces: Remodeling for a New Era - Frank D McCann (Dialogos, 2017)
The history of the Brazilian military has been marked by repeated “reforms” and up-dating efforts to keep abreast of developments abroad.Since World War II such efforts were often weakened, delayed, and reduced by involvement in politics, lack of congressional support, and financial instability.The deep-sea oil discoveries were touted as the beginning of a new era of prosperity that would finally allow growth and modernization of the armed forces.The fall in oil prices likely have made that more of a dream than reality, but even so the armed forces have been moving ahead.Their schools, academies, and institutes are establishing more open relationships with the republic’s universities.The older army institutions, the Escola Preparatória de Cadetes do Exército and the Academia Militar das Agulhas Negras, have reshaped their programs of study and training.In the process their recruitment pattern has changed in ways that may make the officer corps less diverse.The Navy and the Air Force academies seem committed to keeping their programs as they have been.Those services, by their nature, are more technologically oriented than the army, but the army too is more computerized than a decade ago.Brazil is tightening its control of its Amazonian lands, air space, water ways, and ocean.Indeed it is shifting its military focus from the south to the far north and west.Internationally it has adopted U.N. peace-keeping as a consistent part of its set of military missions, the ongoing Haitian assignment being the most ambitious of several in recent decades.It is also accepting some South Americans and Africans as cadets at Agulhas Negras.Given the country’s population the armed forces are small.To expand their size the laws and practices of recruitment would have to change, which seems unlikely.The paper examines Brazil’s current military situation setting it against the history of its evolution.